The Effect of Kinetin Concentration on Eucalyptus pellita F. Muell Micro Cutting Growth (In Vitro) - ridho dzikrana (Jurnal Agroekoteknologi Tropika Lembab, 2018)
Propagation of quality, uniform, and large quantities of Eucalyptus pellita F. Muell seeds as one type of industrial forest plant can be done by tissue culture techniques.  The aim of the study was to determine: 1) the effect of  kinetin concentration on the growth of E. pellita micro cuttings; 2) kinetin concentration which gives the best effect on the growth of E. pellitamicro cuttings.  A single factor experiment, kinetin concentration, was arranged in a Completely Randomized Design (CRD), consisted of five treatments, namely 0; 1; 2; 3; and 4 mg of kinetin L-1 and each treatment was replicated five times.  The variables observed consisted of plant height, leaf color, and number of leaves.  Data were analyzed by analysis of variance (anova) and if the anova was significantly different, to compare between the two treatment averages, followed by a Least Significant Difference  (LSD) test at the level of 5%.  The results showed that different kinetin concentrations had different effects on the height of the culture and number of leaves, but the color of the leaves did not show significant different.  A concentration of  3 mg of kinetin L-1 gave the best effect on the height cuttings at all observation ages: 7; 14; 21; 28; 35; 42; and 49 days after inoculation (DAI) and number of leaves.